2015
DOI: 10.1093/occmed/kqv124
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and psychosocial aspects of work in bank employees

Abstract: Psychosocial conditions in banking activity involving high strain, low social support at work, high effort with low reward and over-commitment may represent possible risk factors for depressive symptoms in bank employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 26 publications
1
26
1
3
Order By: Relevance
“…There is a high level of depressive symptoms in various Chinese occupational groups including nurses, physicians, male correctional officers, university teachers, and underground coal miners [ 11 , 12 , 13 , 14 , 15 , 22 ]. However, there is little research on depression or its related symptoms among bank employees in China and other countries [ 30 ]. The banking sector has been undergoing necessary changes with the development and reform of social economy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high level of depressive symptoms in various Chinese occupational groups including nurses, physicians, male correctional officers, university teachers, and underground coal miners [ 11 , 12 , 13 , 14 , 15 , 22 ]. However, there is little research on depression or its related symptoms among bank employees in China and other countries [ 30 ]. The banking sector has been undergoing necessary changes with the development and reform of social economy.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are a large number of customers in all kinds of banks in China, especially state-owned banks. Working in banks may be a profession that is particularly associated with high stress [ 30 , 31 , 32 ], as a result of intensive concentration, the need to hide negative emotions and answer various questions of customers. Because the state-owned banks have implemented enterprise management patterns that have intensified competition among the banks, front-line bank employees often have to suffer from high workload, and many of them showed high perceived stress and mental health problems [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed employees' experience stress due to a series of big changes took place in financial sector as a result of deregulated markets and globalization of economy affect the working lives of bank employees (Kaur et al, 2017;Hassard et al, 2017). On the other hand, employees' personal and social life affected by job stressors might be attributed to responsibilities for people, poor-peer relations and strenuous working conditions that revealed inverse correlation with performance (Valente et al, 2015;Petarli et al, 2015;Snorradottir et al, 2013;Silva & Navarro, 2012). Further employees' need deficiencies and performance have shown inverse relationship might be attributed to low scores on esteem need, autonomy need, self-actualization need and total-need deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al (2012) observed female employees experienced significantly higher degree of stress than males due to increasing demands at workplace and family pressure. Preshita and Pramod (2014) explained that male and female employees working in public and private sector bank employees experienced stress differently on role stagnation, role erosion and role stagnation contributed to occupational stress in India whereas, Kan and Yu (2016), Valente et al (2015) did not observe significant gender difference. The association amidst job stress and performance discussed in the way that when there are no challenges and no stress; the performance tends to be decrease.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The impact of psychosocial risk factors on the health of workers is more often associated with the onset of cardiovascular diseases [10,11,12] and mental health disorders [13].…”
Section: Introductionmentioning
confidence: 99%